International Symposium on Fluid Acoustics IFA2019 Sopot, Poland, May 20–22, 2019 - 2019, IFA (Archives of Acoustics, 2019)
The symposium included invited lectures, structured sessions and written work covering almost all major areas of fluid acoustics and related issues: research in water environment, using acoustic methods for medical diagnosis, constructing acoustic and ultrasonic research equipment, technical diagnostics, imaging of phenomena occurring in liquids.